Touring is not a vacation - Mohd Azmyl, Md Yusof * (The Malaysian Insight, 2023)
I AM definitely having the post-tour blues. While “blues” may denote “sadness”, a post-tour blues is a combination of happy exhaustion and a lucid state of mind that lasts for approximately two weeks after returning from a tour.